2018
DOI: 10.1161/jaha.117.008163
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis After Melody Valve Implantation in the Pulmonary Position: A Systematic Review

Abstract: BackgroundInfective endocarditis (IE) after transcatheter pulmonary valve implantation (TPVI) in dysfunctioning right ventricular outflow tract conduits has evoked growing concerns. We aimed to investigate the incidence and the natural history of IE after TPVI with the Melody valve through a systematic review of published data.Methods and ResultsPubMed, EMBASE, and Web of Science databases were systematically searched for articles published until March 2017, reporting on IE after TPVI with the Melody valve. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 69 publications
(165 reference statements)
2
48
1
1
Order By: Relevance
“…An in vitro study showed selective adhesion of bacteria to healthy Melody valve tissue (Jalal et al, 2015). The usual microorganisms involved in post-TPVI infective endocarditis are Staphylococci (42% of cases) and Streptococci (30% of cases) (Abdelghani et al, 2018). These values are similar to those observed in prosthetic valve endocarditis cases.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…An in vitro study showed selective adhesion of bacteria to healthy Melody valve tissue (Jalal et al, 2015). The usual microorganisms involved in post-TPVI infective endocarditis are Staphylococci (42% of cases) and Streptococci (30% of cases) (Abdelghani et al, 2018). These values are similar to those observed in prosthetic valve endocarditis cases.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have confirmed the safety of TPVI and the durability of the implant (Patel et al, 2014). However, these benefits are offset by recent reports showing IE after Melody valve implantation (Hascoet et al, 2017;Patel et al, 2014;Abdelghani et al, 2018;Malekzadeh-Milani et al, 2018). The incidence rate of TPVI-related IE varied between 3.5% and 25% in one systemic review, with an annualized rate of 1.3-9.1% per patient-year (Abdelghani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative incidence of infective endocarditis after the Melody valve is reported to be from 3.2% to 25.0%. 2 Thirty-two percent of cases of infective endocarditis occur within 1 year after percutaneous pulmonary valve implantation, 27% occurs in the second year, 18 % occurs in the third year, and 23% occurs beyond 3 years after the procedure. Authors suggested this reflects the fact that the risk is likely not attributable only to surgical factors associated with implantation but also to the mere long-term presence of the protheses.…”
Section: Discussionmentioning
confidence: 99%
“…1 Percutaneous pulmonary valve implantation with the Melody valve is associated with an increased risk of infective endocarditis. [2][3][4][5] The incidence of infective endocarditis in patients after Melody valve is reported to be 3.2-25.0%. 2 Meta-analysis showed higher incidence of infective endocarditis with the Melody valve than Sapien valve (Edwards SAPIEN pulmonic transcatheter heart valve, Edwards Lifesciences, Irvine, California) or surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation